Benefits of the use of tranexamic acid in the treatment of Melasma (Research, Society and Development, 2021)
The skin hyperchromias are frequent sequels due to some disorder in the physiological process of people, among them, hormonal changes, inflammation, allergies, aging, excessive sun exposure. The process of tissue hyperpigmentation occurs due to the increased production of melanin by cells called melanocytes. Melasma is a hyperchromia that affects photo exposed areas of the body, especially the face of women in fertile age, generating an unwanted unaesthetic aspect that directly affects self-esteem. Tranexamic acid has been shown to be an efficient depigmenting agent to lighten people's skin, consequently improving their quality of life. This is an integrative literature review, using as a source of data existing scientific articles in the online platform. Searches were made using the descriptors: melasma, tranexamic acid, hyperpigmentation, in electronic databases, which address the subject of this study: Experimental research that comprove the effectiveness of ATX active in its pure concentration, and with bleaching combinations, through the injectable methods, orally and microagulation, providing the reduction of pigmentary dyschromias, and may improve the results and quality of life of people. Although there are few studies and volunteers about the theme. It is concluded that tranexamic acid is an antiangiogenic active and with potential whitening action that can be administered topically, orally and injected, besides being considered safe. Furthermore, we emphasize the importance of further research related to the topic that can contribute to the creation of safe protocols with the use of the substance by professionals.